First record of Phyllodactylus sentosus (Squamata: Phyllodactylidae) from the Chillón River Valley, Lima, Peru - Olivera, Diego (2016)
Lima Leaf-toed Gecko Phyllodactylus sentosus (Dixon & Huey, 1970), listed as Critically Endangered, has been registered only in some localities between the valleys of the Rímac and Lurín rivers, in the central and southern of Lima city; however its distribution to the north is not documented yet. In the present note we report for first time the presence of P. sentosus in the Huaca Tambo Inga, which is located on the right bank of the Chillón River Valley in the district of Puente Piedra, extending its distribution 19 km to the northeast